The Potential Of Sago (Local Food ) As A Food Substitution In The Meranti Islands District, Riau - Muslim Rahman; Muklis Muklis; M. Rachmadi; Mhd Rafi; Rony Jaya; larbiel hadi (Yayasan Riset dan Pengembangan Intelektual, 2024)
The food crisis is a serious problem in many countries, especially developing countries, even though various steps and policies have been taken to overcome it. Population growth, the intensity of environmental changes such as floods, droughts, extreme variability in temperature or rainfall are triggers for food crises. The threat of a food crisis has an impact on food scarcity, limited food supplie , drastic increases in food and energy prices, high inflation and leading to malnutrition and poverty rates that are difficult to control. However, for Indonesia, apart from the food crisis being a threat, on the other hand the current food crisis could be an opportunity, because Indonesia has substitute food ingredients, one of which is sago, the potential and development of which is in the Meranti Islands Regency, Riau Province. The data analysis technique used to describe the potential of sago and its derivative products is analyzed through SWOT Analysis. The results of this study state that sago is a superior regional product that has enormous opportunities to be developed technically, economically and socially. Technically, the Meranti Islands Regency area is very suitable as a place to grow sago trees with the best quality results in Indonesia. The threat of a food crisis does not apply to Meranti Islands Regency; in fact, the threat has the potential to turn into an economic opportunity. The development of sago as a food substitute requires the role of a government with an entrepreneurial spirit. In the sago development policy and program, the Meranti Islands Regency Government, which has an entrepreneurial spirit, has a Core Strategy, Consequence Strategy, Customer Strategy, Control Strategy and Cultural Strategy. Where this strategy is an embodiment in the form of a technical strategy of the strategy in quadrant II (Diversification) of the SWOT analysis where this position indicates an organization (Meranti Islands Regency) that is strong (sago potential) but still faces big challenges